TIKLUPO a portable seating module for the on-the-go "young-old" senior citizens - Bertulfo, Jasmine Anne C.; Constantino, Nina Elisa B. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2015)
Prolonged standing and walking can lead to serous aches and chronic pains especially to the "young old" group (ages 60 and up) who are considered as the most active and exposed among the senior citizens age groups when it comes to work and outdoor activities. Although there are available chairs such as benches, stools, monoblocs and the like, the problem lies in the fact that there is a lack of elderly-friendly seats in public. This causes the seniors to feel more tired, uncomfortable and less prioritized. This paper demonstrates how a portable chair is integral in a Filipino senior citizen commuter's life.
Thesis (Bachelor of Fine Arts - Industrial Design)--University of the Philippines Diliman
Bibliography : leaf 44.
Keywords: Older people